Effect of Baluran Gum Arabic on Blood Glucose Level in Diabetic Rat (Rattus Novergicus ) - Wiyono, Hidayat Teguh; Utami, Eva Tyas; Wardhani, Dinna Wahyu Putri (BERKALA SAINSTEK, 2021)
Diabetes mellitus is a metabolic disease which indicated with increasing blood glucose level. Carbohidrate, protein, mineral and secondary metabolite (alkaloid, tannin and saponin) can be benefical to treat diabetes mellitus. Rats were randomly divided into three groups. First, control group. Second, STZ group, untreated diabetic. Third, STZ+GA 15% group, diabetic treated with GA 15%. Result showed that blood glucose level before STZ induction on control and STZ group within normal range 78,57±11,90 mg/dL and 74,85±6,86 mg/dL. Blood glucose level significantly increase after STZ induction on STZ and STZ+GA 15% group become 375±6,53 mg/dL and 346,42±50,23 mg/dL. Diabetic rat treated with GA 15% revealed decrease in blood glucose level compared to untreated diabetic rat. Blood glucose level on STZ+GA 15% group continuously decrease become 96,42±13,45 mg/dL and 82,14±9,19 mg/dL. In conclusion, GA 15% could reduce blood glucose level on diabetic rat.